Single Fuel Concept for Croatian Army Ground Vehicles - Spudić, Robert; Somek, Krešimir; Kovačević, Vlado (Promet - Traffic&Transportation, 2008)
During the process of approaching the European associationsand NATO the Republic of Croatia has accepted the singlefuel concept for all ground vehicles of the Croatian Army.Croatia has also undertaken to insure that all aircraft, motorvehicles and equipment with turbo-engines or with pressurizedfuel injection, for participation in NATO and PfP led operationscan • operate using the kerosene-based aviation fuel(NATO F-34). The paper gives a brief overview and the resultsof the earned out activities in the Armed Forces of the Republicof Croatia, the expected behaviour of the motor vehicle andpossible delays caused by the use of kerosene fuel (NATOF-34) as fuel for motor vehicles. The paper also gives the advantagesand the drawbacks of the single fuel concept. By acquiringnew data in the Croatian Armed Forces and experienceexchange with other nations about the method of using fuelF-34, the development of the technologies of engine manufacturingand its vital parts or by introducing new standards in theproductjon of fuels and additives new knowledge will certainlybe acquired for providing logistics support in the area of operations,and its final implementation will be a big step forward forthe Republic of Croatia towards Europe and NATO.